Fasilitasi Penguatan Visi Kolektif BUMDes sebagai Motor Penggerak Ekonomi Masyarakat di Desa Kambiyain Kabupaten Balangan - Sari, Nur Mila; Hamid, Ismar; Hasanah, Tri Febrima; Rusma; Nurhikmah; Fadillah, Muhammad Alfin Rizky; Mu'min, Ahmad; Marfuah; Nabilah, Rifqi Adha; Melani, Andi Maulida; Khairunnisa, Fitri; Khaliq, Muhammad Rafael; Suriani, Anang (Prodi Sosiologi FISIP ULM, 2025)
Rural economic stagnation remains a structural problem faced by many villages in Indonesia, including villages that have relatively adequate natural and human resources, but are not yet supported by participatory and sustainable economic institutions. This condition is also experienced by Kambiyain Village, Tebing Tinggi District, South Kalimantan, where community economic activities are still carried out individually and have not been integrated into a village economic institution that has social and formal legitimacy. The absence of a collective potential management mechanism has implications for the limited economic added value that can be enjoyed equally by the village community. This community service program aims to strengthen the social and institutional foundations of the village economy through the development of a collective vision as a prerequisite for the establishment of a Village-Owned Enterprise (BUMDes). This community service activity was carried out using a participatory approach and qualitative descriptive methods, which lasted for 57 days, from July 17 to September 11, 2025. The stages of the activity included identifying community needs, mapping the potential and problems of the village, confirming initial agreements with stakeholders, conducting education-based socialization activities, utilizing inspirational media in the form of films on BUMDes best practices, and holding focus group discussions (FGD) as a space for community deliberation. The results of the program implementation showed the formation of a BUMDes management structure through an open recruitment mechanism and the formulation of a collective vision agreed upon by the community and the village government, which was then institutionalized in the Articles of Association and Bylaws (AD/ART). These findings confirm that educational and deliberative approaches play an important role in building social legitimacy, increasing community participation and sense of ownership, and strengthening the institutional foundations of the village economy as a prerequisite for the sustainability of BUMDes at the village level.